Exchange-bias via nanosegregation in novel Fe2−xMn1+xAl (x = −0.25, 0, 0.25) Heusler films. Issue 6 (22nd May 2020) - Kurdi, S.; Ghidini, M.; Divitini, G.; Nair, B.; Kursumovic, A.; Tiberto, P.; Dhesi, S. S.; Barber, Z. H.
Abstract : Exchange-bias has been reported in bulk nanocrystalline Fe2 MnAl, but individual thin films of this Heusler alloy have never been studied so far. Abstract : Exchange-bias has been reported in bulk nanocrystalline Fe2 MnAl, but individual thin films of this Heusler alloy have never been studied so far. Here we study the structural and magnetic properties of nanocrystalline thin films of Fe2− x Mn1+ x Al ( x = −0.25, 0 and 0.25) obtained by sputtering and ex situ post-deposition annealing. We find that Fe2 MnAl films display exchange-bias, and that varying Mn concentration determines the magnitude of the effect, which can be either enhanced (in Fe1.75 Mn1.25 Al) or suppressed (in Fe2.25 Mn0.75 Al). X-ray diffraction shows that our films present a mixed L21 –B2 Heusler structure where increasing Mn concentration favors the partial transformation of the L21 phase into the B2 phase. Scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDX) reveal that this composition-driven L21 → B2 transformation is accompanied by phase segregation at the nanoscale. As a result, the Fe2− x Mn1+ x Al films that show exchange-bias ( x = 0, 0.25) are heterogeneous, with nanograins of an Fe-rich phase embedded in a Mn-rich matrix (a non-negative matrix factorisation algorithm was used to give an indication of the phase composition from EDX data). Our comparative analysis of XRD, magnetometry and X-ray magnetic circular dichroism (XMCD), shows that the Fe-rich nanograins and Mn-rich matrix are composed of a ferromagnetic L21 phase and an antiferromagnetic B2 phase, respectively, thus revealing that exchange-coupling between these two phases is the cause of the exchange-bias effect. Our work should inspire the development of single-layer, environmentally friendly spin valve devices based on nanocomposite Heusler films.